2021
DOI: 10.1038/s41380-021-01048-7
|View full text |Cite
|
Sign up to set email alerts
|

Circadian rhythms in bipolar disorder patient-derived neurons predict lithium response: preliminary studies

Abstract: Bipolar disorder (BD) is a neuropsychiatric illness defined by recurrent episodes of mania/hypomania, depression and circadian rhythm abnormalities. Lithium is an effective drug for BD, but 30–40% of patients fail to respond adequately to treatment. Previous work has demonstrated that lithium affects the expression of “clock genes” and that lithium responders (Li-R) can be distinguished from non-responders (Li-NR) by differences in circadian rhythms. However, circadian rhythms have not been evaluated in BD pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 55 publications
1
37
0
Order By: Relevance
“…222 Using peripheral cell cultures and iPSC-derived neurons, circadian rhythm abnormalities have been described in BD, including anomalies in clock gene expression, 223 period, 135,180 phase, 181 and low amplitude. 181,224,225 Similar studies have revealed cellular rhythm abnormalities in SCHZ, 226 alcoholism, 227 Alzheimer's Disease, 228 and ADHD. 229 However, none of these cell-based studies have compared two or more clinical samples directly, and some of the differences in rhythms parameters are distinct.…”
Section: Do Circadian Biomarker Studies Distinguish Bd From Other Psy...mentioning
confidence: 99%
“…222 Using peripheral cell cultures and iPSC-derived neurons, circadian rhythm abnormalities have been described in BD, including anomalies in clock gene expression, 223 period, 135,180 phase, 181 and low amplitude. 181,224,225 Similar studies have revealed cellular rhythm abnormalities in SCHZ, 226 alcoholism, 227 Alzheimer's Disease, 228 and ADHD. 229 However, none of these cell-based studies have compared two or more clinical samples directly, and some of the differences in rhythms parameters are distinct.…”
Section: Do Circadian Biomarker Studies Distinguish Bd From Other Psy...mentioning
confidence: 99%
“…Western blotting of a miR-27a KO cell model and function analysis validated NCAM1 as a direct target in human NPCs. While NPCs 46 play critical roles in bipolar disorder, aberrant neuron functions might also be related to bipolar disorder 47 . Previous studies have identified associations of serum microRNA-27a with cognitive function in a Japanese population 48 and found that NCAM is elevated in the CSF of patients with bipolar type I and unipolar affective disorders 49 .…”
Section: Discussionmentioning
confidence: 99%
“…They observed strong circadian rhythms in Per2-luc expression in NPCs and neurons of LR and controls, but NPC rhythms in LR were shorter whereas NR rhythms were weak and low in amplitude. They found that lithium lengthened the circadian time period in LR and control neurons, but failed to change the rhythms in the lithium NR group [132].…”
Section: Lithium Treatment In Cellular Models Of Bdmentioning
confidence: 98%